Dahsuskim (Kemudahan Khusus Keimigrasian), Kontrol Keimigrasian Terhadap Awak Kapal Asing Dan Tenaga Ahli Asing di Indonesia - Supartini Supartini; Siti Khatijah (Sekolah Tinggi Maritim Yogyakarta, 2017)
Rapid growth of technology in sea transport requires much number of seafarers. Indonesian National Ship owners Association (INSA) claims that the need of seafarers is getting increased hand in hand with Cabotage policy which obliges whether all domestic or national sea transports should use nation-flag vessel and conducted by national sea transport shipping company as well as occupied by Indonesian crews. Shipping agent is needed by foreign shipping company to serve all the vessel needs, crew and ship cargo. Shipping agent also arranges all documents as well as all the crew needs. It deals with the crew when the crew is getting sick, extending expired documents, also arranging letter for special ease of immigration for foreign vessel crew. All crews and foreign expert who work in Indonesia territory should get supervision and control from immigration affair especially those who work using sea transport. The purpose of arranging letter of special ease of immigration is to avoid crimes which are many caused by uncontrolled incoming and outgoing flow of foreign crews. For example it avoids smuggling, illegal immigrant, terrorism, drug abuse which commonly happens in Indonesian immigration territory. Directorate general of immigration even tends to maximize immigration officers in handling the incoming and outgoing flow of foreign workers or foreign crews especially those in foreign vessel. This research belongs to qualitative research with descriptive approach